Tank-top, Indonesian Music Video, and Mythologizing Modern Women: Some Theoretical Notes - Fionna Christabella (Department of Communications, Universitas Islam Indonesia, 2020)
Tank-top has recently become a popular costume in the Indonesian music video. As a theoretical note, this paper shows that music video has been analyzed with two different but interrelated approaches, i.e. contextual and textual analysis. The contextual analysis emphasizes the broader political economy surrounding the production, distribution and consumption of the music video. The textual analysis, which could be conducted in three types of analysis, i.e. narrative, content, and semiotics, focuses on the representation practices in the music video. This study also shows that tank-top, an underwear moved out into outerwear, is a kind of femininity technique, characterized by the appearance and projection of the female body. The use of tank-top in music video shows the ‘new order for intimacy’ through the ‘ritualization of nudity and sexuality’. This phenomenon also examples the way of mythologizing modern women, through which the representation of modern women have become a myth. However, this very construction of modern women is inseparable from the ideological discourses and power relations that naturalize these representational practices. Keywords: Indonesian music video, tank-top, representation, modern women, myth, ideology.